2023
DOI: 10.1111/ene.16051
|View full text |Cite
|
Sign up to set email alerts
|

Prospective follow‐up study of youth and adults with onset of functional tic‐like behaviours during the COVID‐19 pandemic

Christelle Nilles,
Natalia Szejko,
Davide Martino
et al.

Abstract: Background and purposeVery little is known about the long‐term prognosis of patients with functional tic‐like behaviours (FTLBs). We sought to characterize the trajectory of symptom severity over a 12‐month period.MethodsPatients with FTLBs were included in our prospective longitudinal child and adult clinical tic disorder registries at the University of Calgary. Patients were prospectively evaluated 6 and 12 months after their first clinical visit. Tic inventories and severity were measured with the Yale Glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The CGI data gathered at follow‐up visits from August 2022 to January 2023 showed that approximately three‐fourths of patients had improvement in FTLBs, independent of comorbid diagnoses. This is in keeping with findings across other sites (Howlett et al., 2022 ; Nilles et al., 2023 ; Prato et al., 2022 ) and in contrast to tic disorders which tend to be more treatment‐resistant. The cessation of COVID‐19 isolation protocols likely reduced the burden of depression and anxiety.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The CGI data gathered at follow‐up visits from August 2022 to January 2023 showed that approximately three‐fourths of patients had improvement in FTLBs, independent of comorbid diagnoses. This is in keeping with findings across other sites (Howlett et al., 2022 ; Nilles et al., 2023 ; Prato et al., 2022 ) and in contrast to tic disorders which tend to be more treatment‐resistant. The cessation of COVID‐19 isolation protocols likely reduced the burden of depression and anxiety.…”
Section: Discussionsupporting
confidence: 89%
“…This rate of improvement is similar to patients who received therapy without an SSRI or SSNRI (78%). This finding is consistent with well-studied outcomes for anxiety and depression that have shown that treatment with therapy alone is equally effective compared to treatment with SSRIs at 6-month follow-up (March et al, 2007), Other studies have also found that the CBT and SSRIs were effective for promoting symptom improvement (Howlett et al, 2022;Nilles et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A quick recognition of FTLBs versus tics is very important in the clinic, because misdiagnosis of FTLBs can lead to escalation of potentially deleterious treatments. Currently, proposed management of FTLBs includes psychoeducation, behavioral interventions and treatment of mental health comorbidities 17,25,29–31 …”
Section: Discussionmentioning
confidence: 99%